Influence of weed control treatments on available soil nutrient and plant growth parameters of guava (Psidium guajava L.) (Indian Journal of Arid Horticulture, 2023)
This study aimed to evaluate the effects of different weed control methods on soil health and growth parameters in guava cultivation. In this study, 9 years old guava plants of cultivar L-49 at CCSHAU, Hisar were selected during the years 2019-20 and  2020-21. A total of twenty-one treatments were applied on guava trees. Soil and leaf nutrient levels were assessed along with growth parameters including plant height, canopy spread, chlorophyll content anwwd leaf area. Among herbicides, glyphosate (1.26 kg/ha) + carfentrazone (20 g/ha) resulted in the highest levels of N (261.77 and 263.86 kg/ha), Zn (6.79 and 6.80 mg/kg), and Fe (2.26 and 2.28 mg/kg) and  glyphosate (1.26 kg/ha) + oxyfluorfen (100 g/ha) led to the maximum levels of P (30.20 and 31.27 kg/ha) and K (298.67 and 299.66 kg/ha) respectively. The maximum  leaf area (52.21 cm2 and 54.56 cm2) and the greatest increase in plant spread (ranging  from 6.12% to 7.15%) were recorded in the treatment with glyphosate (1.26 kg/ ha) combined with carfentrazone (20 g/ha). The highest increases in plant height were observed with the application of glyphosate (1.26 kg/ha) combined with carfentrazone (20 g/ha) and glyphosate (1.26 kg/ha) combined with oxyfluorfen (100 g/ha), with percentage increases ranging from 6.91% to 7.05% and 6.90% to 7.07%, respectively. Additionally, manual weeding and mulching also resulted in better growth parameters, including increased plant height and canopy spread.
Keywords: Herbicides; guava; weed free; soil nutrients; leaf area